Ternary Transition Metal Sulfide as High Real Energy Cathode for Lithium–Sulfur Pouch Cell Under Lean Electrolyte Conditions. Issue 2 (18th December 2021) - Guo, Hao; Hu, Jing; Yuan, Huimin; Wu, Ningning; Li, Yingzhi; Liu, Guiyu; Qin, Ning; Liao, Kemeng; Li, Zhiqiang; Luo, Wen; Gu, Shuai; Wan, Weihua; et al.
Abstract: Fabrication of a highly porous sulfur host and using excess electrolyte is a common strategy to enhance sulfur utilization. However, flooded electrolyte limits the practical energy density of Li–S pouch cells. In this study, a novel Fe0.34 Co0.33 Ni0.33 S2 (FCN) is proposed as host for sulfur to realize Ah‐level Li–S full cells demonstrating excellent electrochemical performances under 2 µL mg −1 lean electrolyte conditions. Moreover, Kelvin probe force microscopy shows that the FCN surface contains positive charge with a potential of ≈70 mV, improving the binding of polysulfides through Lewis acid base interaction. In particular, the FCN@S possesses inherent electrochemical activity of simultaneous anionic and cationic redox for lithium storage in the voltage window of 1.8–2.1 V, which additionally contributes to the specific capacity. Due to the low carbon content (≈10 wt%), the sulfur loading is as high as ≈6 mg cm −2, approaching an outstanding energy density of 394.9 and 267.2 Wh kg −1 at the current density of 1.5 and 4 mA cm −2, respectively. Moreover, after 60 cycles at 1.5 mA cm −2, the pouch cell still retains an energy of 300.2 Wh kg −1 . This study represents a milestone in the practical applications of high‐energy Li–S batteries. Abstract : A novel Fe0.34 Co0.33 Ni0.33 S2 cathode host possessing excellent polysulfides adsorption capability and rich sulfur vacancies has been prepared. The sulfur loading is as high as ≈6 mg cm −2 and an energy density of 394.9 and 267.2 Wh kg −1 has been achieved at the current density of 1.5 and 4 mA cm −2, respectively, under very lean electrolyte conditions of 2 μL mg −1 .